NAVIGATING THE INTERSECTION OF DIGITAL TRANSFORMATION AND SUSTAINABLE BUSINESS STRATEGY IN EMERGING MARKETS: EVIDENCE FROM UZBEKISTAN - Khasanova Diyora,; Sobiroba Makhsumabonu, (TADQIQOTLAR, 2026)
Abstract The accelerating pace of digital transformation alongside the growing urgency of  sustainability  challenges  has  redefined  the  strategic  priorities  of  modern organizations.  This  study  investigates  the  integration  of  digital  technologies  and sustainable  business  practices  in  emerging  markets,  with  a  particular  focus  on Uzbekistan. By synthesizing existing literature and analyzing regional developments, the  paper  proposes  a  strategic  framework  for  aligning  digital  innovation  with environmental, social, and governance (ESG) objectives. The findings highlight that while emerging markets face infrastructural and institutional constraints, they possess unique  opportunities  to  leapfrog  traditional  development  stages  through  digital adoption.  The  study  further  emphasizes  the  critical  role  of  business  education  in equipping future leaders with the competencies required to manage this transformation. The  article  contributes  to  both  academic  discourse  and  practical  policymaking  by offering insights relevant to managers, educators, and policymakers.